How does artificial intelligence affect the environmental performance of enterprises? Evidence from China - Jiumei Zhai; Jiaxin Huang (Frontiers in Environmental Economics)
Artificial intelligence (AI) serves as a pivotal force restructuring enterprise organization, significantly advancing green transition and promoting sustainable macroeconomic and societal development. This paper empirically examines the effects and transmission channels of AI on firm-level environmental performance, drawing on panel data from Chinese A-share listed firms spanning 2009–2022 and leveraging the establishment of the “National New Generation Artificial Intelligence Innovation Development Pilot Zone” as a quasi-natural experiment within a difference-in-differences (DID) framework. Results demonstrate that AI adoption significantly improves firms' environmental performance. Mechanism analysis indicates that AI facilitates this improvement primarily through enhanced market integration and the stimulation of green innovation activities. Heterogeneity analysis further reveals that the positive impact of AI on environmental performance is more substantial among firms in non-heavy-polluting and capital-intensive sectors.